Analisis Penggunaan Kata Tabu Dialog Jawa Timuran dalam Cuplikan Youtube “Yowis Ben 2” (Kajian Sosiopragmatik) - Kasmanah; Muhammad Kamal bin Abdul Hakim; Miftahulkhairah Anwar (CV Putra Publisher, 2022)
The language used as a medium of communication for someone to convey ideas or thoughts must pay attention to the norms, situations, and conditions of the language being spoken. Because inaccuracy in using language often triggers conflict in certain communities. This can be influenced by the development of language and culture such as the emergence of taboo words that are not appropriate in using and interpreting them. In the upload of the YouTube channel